UPLC-ESI/MS/MS Profiling and Anti-Inflammatory Activity of Gleditsia caspica - Hager Ashraf; Ashaimaa Moussa; Amany Seleem; Omayma A. Eldahshan; Abdel-Nasser Singab (Ain Shams University, 2020)
The Caspian Locust is the common name of Gleditsia caspica, a tree cultivated in the southern and western Caspian Sea in Russia and Iran. Herein, a qualitative characterization of the chemical constituents of Gleditsia caspica leaves extract using ultra-performance liquid chromatography coupled to electrospray ionization tandem mass fragmentation (UPLC-ESI/MS/MS) analysis was performed revealing the presence of nine compounds: six flavonoids, one triterpenoid, one phytosterol, and one long chain ester. Six compounds were newly reported from Gleditsia caspica and two for the first time from genus Gleditsia. Moreover, the in-vivo anti-inflammatory activities of two different doses; 50 and 100 mg/kg of the aqueous-alcoholic extract of Gleditsia caspica leaves were evaluated in the carrageenan-induced paw edema model. The percentage of edema inhibition was calculated after 1, 2, 3, and 4 h of the administration showing a significant reduction in edema thickness in a dose and time-dependent manner compared to the control drug, indomethacin. These results put forward Gleditsia caspica extract as a potential natural anti-inflammatory agent with minimal side effects.